Sub-structure-based 'three-tiered' finite element approach to soil-masonry-wall interaction for light seismic motion. (15th October 2021) - Longo, Michele; Sousamli, Marianthi; Korswagen, Paul A.; van Staalduinen, Piet; Rots, Jan G.
Highlights: Equivalent soil-structure interaction for modelling vibrations in masonry buildings. Preservation of the vibration properties leading to rocking and elongation. Non-linear masonry model to assess (light) damage. Decoupled soil and structural models for efficient, fast (probabilistic) analyses. Abstract: Recent, light earthquakes induced by the extraction of gas in the north of the Netherlands have been linked to light, mostly aesthetic damage of the traditional masonry structures in the region; this is also connected to economic losses and societal unrest. To be able to accurately assess the light damage, detailed finite element models are necessary and need to include realistic soil movement, wave propagation, and soil-structure interaction boundaries. Moreover, the minute deformation of the soil, including the rocking and translational components of seismic ground motion, has shown to be influential to light damage. Consequently, this study has pursued the definition of efficient soil-structure interaction boundaries to implement in finite element models of buildings. A methodology, following the sub-structure method for the seismic Soil-Structure-Interaction (SSI) is defined and presented. The soil-structure-system is divided into three sub-systems: the far-field soil, the near-field soil and the superstructure. First, a 3 km deep and 8 km wide, plane-strain model of the soil is employed to study the behaviour of the soil at the surface due to deep, simplified seismic events. The soil model is linear-elastic since only light seismic excitations are considered. Next, a smaller, 30 × 300 m (shallow) soil model with a building on top, is given boundary elements calibrated to replicate the behaviour observed at the surface in the larger model. Finally, 2D models of masonry façades set on the intermediate soil model are used to reduce the soil-structure interaction to representative interface elements. The models are matched in terms of dynamic behaviour, strains, cracking, and displacements, and the behaviour is compared to existing ground motion data for the Zeerijp and Westerwijtwerd earthquakes. It is demonstrated that the equivalent interface allows efficient modelling of seismic excitations considering a detailed soil-structure interaction for complex, smeared non-linear, time-history analyses of wall models to assess (light) damage in probabilistic studies. Models with this equivalent interface show greater damage than comparison models without it.